The Effect of Carbon Black, Graphite Content on the ThermalConductivity of (Epoxy- Carbon Black, Epoxy – Graphite) Composites - Al-Shammry, Z. (Iraqi Journal of Science, 2025)
The thermal conductivity of Epoxy filled with carbon black and graphitematerials are measured in order to study the effect of these particles on the thermalconductivity of these composite materials. With the increase of content of fillerparticles, the amount of formed conductive chains increases then the conductivechain tends largely to increase the thermal conductivity of a composite.